2021
DOI: 10.22159/ajpcr.2021.v14i1.40318
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Body Mass Index in Children – A Community-Based Study

Abstract: Objectives: The increasing prevalence of overweight, obesity, and underweight in children has implications for their future health and it is vital to understand the modifiable factors that contribute to it. The study’s main objective is to determine the factors associated with the body mass index in children. Methods: A cross-sectional study was conducted among 346 school children over a period of 6 months. Data were collected using self-administered questionnaire. Physical measurements such as height an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Moreover, different obesity measurements are used in different studies like body mass index (BMI), fat mass and waist circumference. While it has been reported that BMI is one of the simplest and extensively used screening tool for child and adult obesity and it is not only used as an outcome measure for determining obesity but also as a useful anthropometric index for cardiovascular risk ( 30 ). Also, because of its simplicity, BMI is a standard tool to diagnose overweight/obesity as declared by WHO ( 6 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different obesity measurements are used in different studies like body mass index (BMI), fat mass and waist circumference. While it has been reported that BMI is one of the simplest and extensively used screening tool for child and adult obesity and it is not only used as an outcome measure for determining obesity but also as a useful anthropometric index for cardiovascular risk ( 30 ). Also, because of its simplicity, BMI is a standard tool to diagnose overweight/obesity as declared by WHO ( 6 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends children and adolescents to have at least one hour of moderate to vigorous physical activity per day and vigorous-intensity physical activity at least three times per week [4]. Nonetheless, nowadays, the time spent actively is increasingly being replaced by screenbased media, and screen time has increased in both children and adolescents with a pronounced role in obesity promotion worldwide [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%